2012
DOI: 10.1182/blood-2011-07-360594
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of recombinant factor VIII: the relationships of pharmacokinetics to age and body weight

Abstract: Comparison of the pharmacokinetics (PK) of a coagulation factor between groups of patients can be biased by differences in study protocols, in particular between blood sampling schedules. This could affect clinical dose tailoring, especially in children. The aim of this study was to describe the relationships of the PK of factor VIII (FVIII) with age and body weight by a population PK model. The potential to reduce blood sampling was also explored. A model was built for FVIII PK from 236 infusions of recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
289
2
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(321 citation statements)
references
References 28 publications
26
289
2
4
Order By: Relevance
“…They have been built independently and separately and are characterized by different covariates. The structural PopPK models for rAHF-PFM [15] and rFVIIIFc [16] are two-compartmental models with the primary PK parameters being clearance (CL), volumes of distribution of the central and peripheral compartment (V 1 , V 2 ), and intercompartmental clearance (Q). The model for rAHF-PFM uses body weight and age as covariates on clearance and body weight as covariate on V 1 and V 2 .…”
Section: Methodsmentioning
confidence: 99%
“…They have been built independently and separately and are characterized by different covariates. The structural PopPK models for rAHF-PFM [15] and rFVIIIFc [16] are two-compartmental models with the primary PK parameters being clearance (CL), volumes of distribution of the central and peripheral compartment (V 1 , V 2 ), and intercompartmental clearance (Q). The model for rAHF-PFM uses body weight and age as covariates on clearance and body weight as covariate on V 1 and V 2 .…”
Section: Methodsmentioning
confidence: 99%
“…9 In the prophylactic setting, Carlsson et al have shown that FVIII consumption can be significantly reduced by application of pharmacokinetic (PK) modeling to individualize dosing regimens. [11][12][13][14] In the perioperative setting, Longo et al have reported excessive FVIII consumption and clearance in 50% of surgical hemophilia patients due to unidentified factors. 15 This suggests mechanisms of increased clearance due to hemostatic challenges during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent article by Gringeri et al [1] entitled 'Recombinant full-length factor VIII (FVIII) and extended half-life FVIII products in prophylaxis -new insight provided by pharmacokinetic modelling', the authors present data from simulations based on independent population pharmacokinetic models for rAHF-PFM [2], a third-generation standard half-life recombinant FVIII (rFVIII) therapy, and rFVIII Fc fusion protein (rFVIIIFc) [3], a prolonged half-life rFVIII. These simulations predict that dosing patients with an extended half-life FVIII product at 1.5-fold longer intervals compared with a standard half-life FVIII product (i.e.…”
mentioning
confidence: 99%
“…The clinical data for rFVIIIFc clearly demonstrate that patients treated prophylactically with rFVIIIFc can achieve low bleeding rates with fewer infusions. Combined factor V (FV) and FVIII deficiency (F5F8D), characterized with simultaneous decreases of FV and FVIII activity to 5-30% of normal plasma [1], generally has spontaneous bleeding and excessive bleeding after trauma or surgery [2,3]. F5F8D is a rare bleeding disease first reported in 1954 [4].…”
mentioning
confidence: 99%